In-class simulations of the iterated prisoner's dilemma game - Bodo, Peter (Journal of Economic Education, 2002)
The author developed a simple computer program for the in-class simulation of the repeated prisoner's dilemma game with student-designed strategies. He describes the basic features of the software and presents two examples for the use of the program in teaching the problems of cooperation among profit-maximizing agents.
Keywords: Computer simulation; Experiments; Prisoner's dilemma; Repeated games; dept.eco; dept.fin

Exchange rate adjustment in partially liberalized economy - Grubacic, Sanja (Economics of Planning, 2002)
This paper develops a model of exchange rate determination in partially liberalized post-socialist economy that operates under soft budget constraints in nontradable sectors. The model captures the factors that determine the evolution of a country's external balance during the initial phase of economic liberalization. Three types of disturbances are the center of analysis: liberalization of trade and foreign exchange regime, devaluation, and price liberalization. We show that the real exchange rate appreciation may either improve or worsen the trade balance depending on the sources of this appreciation. Thus, we argue that the real exchange rate cannot reflect true country's competitiveness unless all sectors are equally exposed to hard budget constraints. The model implications are further analyzed through the empirical evidence on the relationship between the real exchange rate and trade balance in three selected East European countries.
Keywords: Europe; Exchange rate; External balance; Liberalization; Post-socialist economy; Soft budget constraint; balance of trade; competitiveness; dept.eco; dept.fin; exchange rate; external balance; liberalization; post-socialist economy; real exchange rate; soft budget constraint